#### Answer

$y^{8}$

#### Work Step by Step

$\sqrt[6] (y^{48})=y^{8}$
We know this because $(y^{8})^{6}=y^{8\times6}=y^{48}$

Published by
Pearson

ISBN 10:
0321785045

ISBN 13:
978-0-32178-504-6

$y^{8}$

$\sqrt[6] (y^{48})=y^{8}$
We know this because $(y^{8})^{6}=y^{8\times6}=y^{48}$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.